Caracterização do tamarilho (Solanum betaceum Cav.) e agregação de valor com elaboração de geleia - Goulart, Nádjla Miranda Vilela (2019)
Tamarillo (Solanum betaceum Cav.) belongs to the Solanaceae family and its culture attracted interest for presenting juicy and tasty fruits, with characteristic acid taste. With the current need to reduce sugar in foods, and given the economic and nutritional importance of fruits of the Cerrado, the objective was to characterize yellow tamarillo fruits in different stages of development, as well as to produce and characterize different elaborated tamarillo jellies and added strawberry and passion fruit, in extra and light formulations, in order to add value and evaluate their physicochemical and sensory characteristics. A completely randomized design with three replications was used for the analysis of tamarillo and jellies, and for the sensory analysis a randomized block design was used. During the fruit ripening there was influence of developmental stages (p <0.05), where it was found a decrease in pH and respiratory activity, increase in titratable acidity and soluble solids. Decreased pectinamethylesterase activity was also observed concomitantly with increased polygalacturonase activity, and a consequent increase (p <0.05) in total and soluble pectin levels in the more advanced stages of maturation, which were marked by progressive loss of firmness of the fruits. As for color, there was an increase (p <0.05) in the values of a *, b * and C * indicating a tendency of reddish orange coloration, due to the degradation of chlorophyll and the presence of carotenoids, which increased its content at intermediate stage maturation with subsequent fall in the already mature tamarillo. In general, there was a decrease in phenolic compounds and antioxidant capacity accompanied by an increase in vitamin C content. The proximate composition was marked by the high moisture content. The parameters analyzed during maturation reinforce those already found in studies with yellow tamarillo and other varieties, highlighting their technological potential. To evaluate the jellies, six treatments were performed: A (extra tamarillo jelly); B (light tamarillo jelly); C (extra passion fruit tamarillo jelly); D (light tamarillo jelly with passion fruit); E (extra strawberry tamarillo jelly) and F (light strawberry tamarillo jelly). Among the treatments, it was observed that C, D, E and F presented higher acidity; A, C, and E presented higher soluble solids content and lower moisture content. Treatments A, B, E, and F presented higher vitamin C content. As for phenolic compounds, samples E and F presented higher content in relation to the others. The antioxidant capacity was equal (p> 0.05) in all treatments. A higher total carotenoid content was observed in treatment D. Regarding phenolic compounds, antioxidant activity and carotenoids, lower levels were observed in jelly than in fresh fruit due to the cooking process. Treatments A, B, C, D presented yellowish coloration and E and F, reddish coloration, in general, all samples presented intense coloration. It was found difference (p< 0.05) between the treatments regarding texture profile, where A, C, E presented firm texture and B, D, F expressed a more fragile texture, corroborating the results of the sensorially evaluated texture. For the sensory tests, it was observed that in general the frequency of sensory acceptance was between the scores 6 (slightly liked) and 8 (very liked), being the jams A, C and E the ones with the highest sensory acceptance. It was concluded that the use of the CATA descriptive method suggested complementary information presenting positive and negative characteristics that contributed to the acceptance of the jams.